Os desafios docentes na escolarização de estudantes indígenas na escola urbana Paulo Freire em Imperatriz – Maranhão - BORGES, Adriano da Silva (2022)
Line of Research: Pluriculturality, Interculturality and Interdisciplinary Educational Practices. The objective of this study is to understand the challenges faced by teachers in the schooling of indigenous students in their classrooms, with the Paulo Freire Municipal School (EMPF)3 as the locus of research, which has the largest number of indigenous students enrolled in an urban school in Imperatriz. Maranhão because it is close to the only urban village, Aldeia Amazonas4 . To do so, it starts with the following question: How do urban schools in the municipality of Imperatriz face the challenge of schooling indigenous students? Methodologically, it is characterized as action-research carried out in the school for teachers who receive indigenous students, using as a resource of bibliographic research to assist in writing the reasoning of the objects, observation, interview and field visits in the urban village where they are located. living the indigenous people who study at the school. The study presents different views of authors as a critical theoretical basis and reflection in view of the relationship between the researched subjects such as: Zaparoli (2016) Ferreira (2001); Gomes (2012); Monteiro (2001); Freire, (1980); Laraia (2004) Albuquerque (2011); Mussi (2011), among other researchers who contextualize with educational policies aimed at indigenous peoples in schools, in this sense recognizing the guidelines that are being worked with teachers in relation to the National Curriculum Guidelines for Indigenous School Education (EEI) (BRAZIL , 2008) and the Federal Constitution specific to Indigenous Peoples (BRASIL, 1988), Laws of Guidelines and Bases for National Education (LDB) Law No. 9,394 (BRASIL, 1996), National Education Plan (PNE) in Law No. 10,172 (BRASIL, 2001), Law 11.645 (BRASIL, 2008) in order to understand how the applicability in the exercise of Indigenous School Education (EEI) with a bias in pluri and Interculturality is being. The results of the study converged to the affirmation of the research object, that the challenges faced by teachers who receive indigenous students along with non-indigenous students in the urban school Escola Municipal Paulo Freire (EMPF), such as mother tongue and diversity of cultural situations, geographic areas of indigenous peoples, in addition to the difficulties of the Portuguese language L2. Including the emergence of the elaboration of public educational policies aimed at access and remaining in school spaces for indigenous peoples who are studying with non-indigenous people in an urban context.